Radiation from relativistic positrons during planar channeling in crystals - Boldyshev, V.F.; Shatnev, M.G. (Вопросы атомной науки и техники, 2004)
We present a detailed calculation of channeling radiation of planar-channeled positrons from crystal targets in the framework of our approach, which was proposed recently.